2020
DOI: 10.3390/s20041208
|View full text |Cite
|
Sign up to set email alerts
|

Using Domain Knowledge for Interpretable and Competitive Multi-Class Human Activity Recognition

Abstract: Human activity recognition (HAR) has become an increasingly popular application of machine learning across a range of domains. Typically the HAR task that a machine learning algorithm is trained for requires separating multiple activities such as walking, running, sitting, and falling from each other. Despite a large body of work on multi-class HAR, and the well-known fact that the performance on a multi-class problem can be significantly affected by how it is decomposed into a set of binary problems, there ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In [9] used the normalized confusion matrix of LSTM in applying a hierarchical agglomerative clustering algorithm for automatic tree taxonomy building without providing enough details. The authors in [52] showed that using any HC produces better performance than FC. It also showed by examining different hierarchy taxonomies that changing the taxonomy will not yield significant improvement.…”
Section: B Hierarchical Classification (Hc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [9] used the normalized confusion matrix of LSTM in applying a hierarchical agglomerative clustering algorithm for automatic tree taxonomy building without providing enough details. The authors in [52] showed that using any HC produces better performance than FC. It also showed by examining different hierarchy taxonomies that changing the taxonomy will not yield significant improvement.…”
Section: B Hierarchical Classification (Hc)mentioning
confidence: 99%
“…When flat or LCL classification methods are used, such types always suffer from high misclassification rates. Although LCPN could propagate the errors from one level to the next, its overall accuracy would still be higher than the flat classification [55]. This approach is preferable for researchers in the HAR domain who consider hierarchical classification for its lower complexity [13].…”
Section: ) Local Classifier Approachmentioning
confidence: 99%
“…Recent research on activity recognition has employed wearable sensors for activity data collection, with the most common sensor device being an accelerometer. 24,25,26 An accelerometer is a device that measures the acceleration of an entity. Other sensor devices include gyroscopes, magnetometers, electrocardiography monitors, and many others.…”
Section: Related Workmentioning
confidence: 99%
“…As an advantage, considering these classes paired together as opposed to the flat classification setting leads to significant degradation of recognition performances as demonstrated in some works around the SHL dataset [23]. In contrast, organizing the various concepts into a tree-like structure, inspired by domain expertise, demonstrated significant gains in terms of recognition performances in the context of the SHL challenge [12] and activity recognition in general [15,16].…”
Section: Problem Formulation and Backgroundmentioning
confidence: 99%